251 Oxidation of energy substrates in tissues of Largemouth bass (Micropterus salmoides). (5th December 2019) - Li, Xinyu; Wu, Guoyao
Abstract: Because of growing interest in producing Largemouth bass (HMB) as a source of high-quality protein for human consumption worldwide, it is imperative to understand the metabolism of nutrients (including amino acids and carbohydrate) in this aquatic animal. The present study tested the hypothesis that amino acids are oxidized at a higher rate than carbohydrates (e.g., glucose) and fatty acids (e.g., palmitate) to provide ATP for tissues of LMB fed a 45%-crude protein diet. The liver, intestine, kidney, and skeletal muscle were isolated from juvenile LMB and incubated at 26 °C (the body temperature of LMB) for 2 h in 1 ml of oxygenated Krebs–Henseleit bicarbonate buffer (pH 7.4) containing a mixture of nutrients (2 mM glutamate, 2 mM glutamine, 2 mM aspartate, 2 mM alanine, 2 mM leucine, 5 mM glucose, and 2 mM palmitate). The rate of oxidation of each energy substrate was determined by using [U- 14 C]-labeled glutamate, glutamine, aspartate, alanine, leucine, glucose, or palmitate and collecting 14 CO2 from each tracer. Results indicated that aspartate, glutamate and glutamine were extensively oxidized in all the four tissues and contributed to 67% of total ATP production. Glutamate contributed to more ATP than glutamine in the intestine, whereas similar amounts of ATP were produced from glutamate and glutamine in the liver, kidneys and skeletal muscle. In all the four tissues, rates of oxidation of alanine, leucine, palmitate and glucose were low and each of those nutrients contributed to < 10% of total ATP production. Together, the oxidation of aspartate, glutamate, glutamine, alanine plus leucine provided 82–85% of total ATP for the liver, intestine, kidney, and skeletal muscle. We conclude that amino acids, rather than glucose and long-chain fatty acids, are the primary energy substrates in the major tissues of Largemouth bass.